Dexmedetomidine Versus Propofol for Patients With Sepsis Requiring Mechanical Ventilation: A Systematic Review and Meta-Analysis - Huang, Po; Zheng, Xiangchun; Liu, Zhi; Fang, Xiaolei (Frontiers in Pharmacology, 2021)
Purpose: This meta-analysis was performed to access the influence of dexmedetomidine versus propofol for adult patients with sepsis undergoing mechanical ventilation. Materials and Methods: NCBI PUBMED, Cochrane Library, Embase, China National Knowledge Internet (CNKI) and China Biological Medicine (CBM) were searched. Revman 5.3 and Stata software (version 12.0, Stata Corp LP, College Station, TX, USA) were used for meta-analysis. Results: 15 studies were included and the data from the included studies was incorporated into the meta-analysis. And, the result shows that compared with propofol, dexmedetomidine doesn’t reduce 28-day mortality (risk ratios (RR) =0.97, 95% confidence interval (CI) =0.83-1.13, p=0.70). However, our analysis found that dexmedetomidine could reduce Intensive care unit (ICU) stays (standard mean difference (SMD) : -0.15; 95% CI: [-0.30-(-0.01)], p=0.03), duration of mechanical ventilation (SMD: -0.22; 95% CI: [-0.44-(-0.01)], p=0.043), Sequential Organ Failure Assessment (SOFA) (SMD: -0.41; 95% CI: [-0.73-(-0.09)], p=0.013), levels of Interleukin-6 (IL-6) at 24h (SMD: -2.53; 95% CI: -5.30-0.24, p=0.074), and levels of CK-MB at 72h (SMD: -0.45; 95% CI: [-0.83-(-0.08)], p=0.017). Conclusions: This meta-analysis (MA) suggests that in terms of 28-day mortality, sepsis patients with the treatment of dexmedetomidine did not differ from those who received propofol. In addition, more high-quality trials are needed to confirm these findings.